Arthaśāstra paribhāṣa : Iṅgrājī-Oḍia = Glossary of economics : English-Oriya (Commission for Scientific and Technical Terminology, Ministry of Human Resource Development, Dept. of Secondary Education and Higher Education, Govt. of India, 2003)
Glossary of economic terms